VD_FINDINFO Décision / 2015 / 349 vom 5. Mai 2015 - VD Tribunal cantonal (2015)
RÉCUSATION, RISQUE DE COLLUSION, RISQUE DE RÉCIDIVE | 221 al. 1 let. b CPP (CH), 221 al. 1 let. c CPP (CH), 56 let. f CPP (CH)